Lost Lake - Allen, Sarah Addison (St. Martin's Press, 2014)
"Suley, Georgia, is home to Lost Lake Cottages and not much else. Which is why it's the perfect place for newly-widowed Kate and her eccentric eight-year-old daughter Devin to heal. Kate spent one memorable childhood summer at Lost Lake, had her first almost-kiss at Lost Lake, and met a boy named Wes at Lost Lake. It was a place for dreaming. But Kate doesn't believe in dreams anymore, and her Aunt Eby, Lost Lake's owner, wants to sell the place and move on. Lost Lake's magic is gone. As Kate discovers that time has a way of standing still at Lost Lake, can she bring the cottages--and her heart--back to life? Because, sometimes the things you love have a funny way of turning up again. And sometimes you never even know they were lost . . . until they are found"--